Hermetiske reformationer i det 15.-16. århundrede - Tim Rudbøg (Religionsvidenskabeligt Tidsskrift, 2018)
ENGLISH ABSTRACT: This article seeks to nuance the classic narrative of the Reformation in which Martin Luther is singled out and the Reformation, directly linked to Luther, is equally portrayed as a very specific singular event. Based on a perspective of pluralism this article shows that several reformative attempts inspired by Hermetism and the notion of a prisca theologia had already begun prior to Luther and was subsequently continued in connection with the Counter-Reformation and in other circles. Persons such as Marsilio Ficino and Pico della Mirandola and later heirs of Hermetism, are for example only very rarely mentioned directly in connection with the ongoing reformations of the Church. The reason why these persons are overlooked might be rooted in the concept of the Reformation itself and the Christian antipathy for the foreign pagan traditions by which these very persons sought to reform the Church.